Intake of Dietary Fiber From Grains and the Risk of Hypertension in Late Midlife Women: Results From the SWAN Study - Du, Peng; Luo, Kaifeng; Wang, Yali; Xiao, Qi; Xiao, Jiansheng; Li, Yong; Zhang, Xingjian (Frontiers in Nutrition, 2021)
Background: The possible effects of dietary fiber intake on hypertension have not been fully clarified. The association of dietary fiber intake with hypertension risk in midlife women was analyzed in present study. Methods: Baseline data were obtained from the Study of Women’s Health Across the Nation (SWAN). Smooth curve, linear regression and logistic regression analyses were carried out to investigate the associations of 4 indexes of daily dietary estimate (DDE) dietary fiber (dietary fiber intake, dietary fiber intake from beans, dietary fiber intake from vegetables/fruit and dietary fiber intake from grains) with blood pressure in the midlife women. Results: Our study included 2159 participants with an average age of 46. The smooth curve showed approximate negative correlations between the 3 fiber indexes (DDE dietary fiber, DDE fiber from vegetables/fruit and DDE fiber from grains) and blood pressure including diastolic blood pressure (DBP) and and diastolic blood pressure (SBP) respectively (All P<0.005). There were also approximate negative correlations between the 2 fiber indexes (DDE dietary fiber and DDE fiber from grains) and the risk of diastolic hypertension and systolic hypertension (all P<0.05). Furthermore, multiple linear regression analysis suggested DDE dietary fiber (Sβ=-0.057, 95%CI -0.194 - -0.012, P=0.027), DDE fiber from vegetables/fruit (Sβ=-0.046, 95%CI -0.263 - -0.007, P=0.039) and DDE fiber from grains (Sβ=-0.073, 95%CI -0.600 - -0.099, P=0.006, Model 4) were still negatively correlated with DBP respectively after adjusting confounding factors. Only DDE fiber from grains was independently and negatively associated with SBP (Sβ=-0.060, 95%CI -0.846, -0.093, P=0.015) after these same confounding factors were adjusted. Importantly, multiple logistic regression analysis suggested that only higher DDE fiber from grains was independently associated with the reduced risk of diastolic hypertension (OR = 0.848, 95% CI 0.770-0.934, P=0.001, Model 4) and systolic hypertension (OR = 0.906, 95% CI 0.826-0.993, P=0.034, Model 4) after adjustments were made confounding. Conclusions: We results found that increased dietary fiber intake, especially for DDE fiber from grains, contributes lower risk of systolic hypertension and diastolic hypertension respectively in midlife women.